Selenium–Chondroitin Sulfate Nanoparticles Inhibit Angiogenesis by Regulating the VEGFR2-Mediated PI3K/Akt Pathway - Xia Zheng; Xiaofei Liu; Zhuo Wang; Rui Li; Qiaoli Zhao; Bingbing Song; Kit-Leong Cheong; Jianping Chen; Saiyi Zhong (Marine Drugs)
Chondroitin sulfate (CS), a class of glycosaminoglycans covalently attached to proteins to form proteoglycans, is widely distributed in the extracellular matrix and cell surface of animal tissues. In our previous study, CS was used as a template for the synthesis of seleno-chondroitin sulfate (SeCS) through the redox reaction of ascorbic acid (Vc) and sodium selenite (Na2SeO3) and we found that SeCS could inhibit tumor cell proliferation and invasion. However, its effect on angiogenesis and its underlying mechanism are unknown. In this study, we analyzed the effect of SeCS on tube formation in vitro, based on the inhibition of tube formation and migration of human umbilical vein endothelial cells (HUVECs), and evaluated the in vivo angiogenic effect of SeCS using the chick embryo chorioallantoic membrane (CAM) assay. The results showed that SeCS significantly inhibited the angiogenesis of chicken embryo urothelium. Further mechanism analysis showed that SeCS had a strong inhibitory effect on VEGFR2 expression and its downstream PI3K/Akt signaling pathway, which contributed to its anti-angiogenic effects. In summary, SeCS showed good anti-angiogenic effects in an HUVEC cell model and a CAM model, suggesting that it may be a potential angiogenesis inhibitor.